2022
DOI: 10.3390/biomedicines10071640
|View full text |Cite
|
Sign up to set email alerts
|

Optical Behavior of Human Skin Substitutes: Absorbance in the 200–400 nm UV Range

Abstract: The most recent generation of bioengineered human skin allows for the efficient treatment of patients with severe skin defects. Despite UV sunlight can seriously affect human skin, the optical behavior in the UV range of skin models is still unexplored. In the present study, absorbance and transmittance of the UGRSKIN bioartificial skin substitute generated with human skin cells combined with fibrin-agarose biomaterials were evaluated for: UV-C (200–280 nm), -B (280–315 nm), and -A (315–400 nm) spectral range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Bioartificial tissues based on fibrin‐agarose biomaterials displayed an elastic behavior and its modulus of Young was comparable to native tissues, 11 and our previous time‐course analysis carried out for 4 weeks demonstrated that these properties remained stable upon the time in culture 9 . In addition, the optical characterization UGRSKIN model showed that the epidermal layer was able to mature and differentiate being able to absorb most of the incoming UV light, as it is the case of the native skin 10 . When grafted in vivo on immune‐deficient animal models, UGRSKIN demonstrated to be highly biocompatible and able to contribute to skin regeneration 8 .…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Bioartificial tissues based on fibrin‐agarose biomaterials displayed an elastic behavior and its modulus of Young was comparable to native tissues, 11 and our previous time‐course analysis carried out for 4 weeks demonstrated that these properties remained stable upon the time in culture 9 . In addition, the optical characterization UGRSKIN model showed that the epidermal layer was able to mature and differentiate being able to absorb most of the incoming UV light, as it is the case of the native skin 10 . When grafted in vivo on immune‐deficient animal models, UGRSKIN demonstrated to be highly biocompatible and able to contribute to skin regeneration 8 .…”
Section: Introductionmentioning
confidence: 66%
“…This skin model was characterized ex vivo and in vivo in laboratory animals using several histological, histochemical, immunohistochemical, and other analysis methods able to demonstrate that the model was safe and efficient. [8][9][10] In fact, our preclinical studies demonstrated that the biochemical properties and histological structure of the UGRSKIN skin model were similar to the native human skin at both, the epidermal and the dermal layers. Ex vivo, UGRSKIN showed to be biomechanically comparable to the native human skin, with adequate properties as determined by compressive and shear tests.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Quantitative analyzes were performed using ImageJ software (version 1.53 k, National Institute of Health, Bethesda, MD) and following standardized protocols previously described (Carriel et al, 2014; Ortiz‐Arrabal et al, 2021; Rodriguez‐Pozo et al, 2020; Ruiz‐López et al, 2022; Chato‐Astrain et al, 2023; Ortiz‐Arrabal et al, 2023). Briefly, the histomorphological features of the POM and OOM was assessed measuring epithelial length, thickness, and cell area, as well as rete ridge/papillae dimensions.…”
Section: Methodsmentioning
confidence: 99%